“Marianne Knight | Godmersham Park”: Inscription as Community Interface in the Books of Jane Austen’s Niece - Kavanagh, Francesca (Australasian Journal of Victorian Studies, 2020)
In the extant family library of the Knights, the descendants of Jane Austen’s brother Edward, 14 volumes bear the name Marianne Knight. This middle daughter, born at the beginning of the nineteenth century and living into its final decade, remained unmarried all her life. Her inscriptions in the Knight Collection provide keen insight into the ways in which unmarried Victorian women used their books as textual spaces in which to negotiate their precarious social position. Utilizing studies in annotation, affect theory and gift-giving, this article reads Marianne Knight’s inscriptions as interfaces between her personal claims of ownership over texts and their textual space, and two communities of readers through whose hands her books circulated: the line of male inheritors of her father’s property and therefore also Marianne’s books, and unmarried women within the family contemporaneous with Marianne who participated in networks of gift-giving. I argue that Marianne uses the spatial qualities of her inscriptions to assert her position in relation to these two communities by both pushing back against the patrilineal dictates of inheritance and recording acts of intimacy and affection between herself and other unmarried women. By figuring the act of inscription as a negotiation of textual and social space, I expand understandings of nineteenth-century women’s engagement with annotation.